2018
DOI: 10.1002/pat.4371
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of highly cross‐linked hydrophilic porous microspheres poly(N,N′‐methylenebisacrylamide) and poly(N,N′‐methylenebisacrylamide‐co‐acrylic acid) with an application on the removal of cadmium

Abstract: An effective polymerization system was developed for the synthesis of highly cross‐linked hydrophilic monodispersed microspheres with both the micropores and mesopores inside. A series of poly(N,N′‐methylenebisacrylamide) (PMBA) microspheres with the diameters ranging from 100 to 300 nm were synthesized by distillation precipitation polymerization with N,N‐dimethylacetamide (DMAC) as the porogen, acetonitrile as the solvent, and MBA as the cross‐linker and monomer. The particle size, morphology, and porosity v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, the utilization of EGDMA as a crosslinking agent in AN-VBC copolymer system has never been reported before. It was widely reported that the most common crosslinkers that have been used in the polymeric system are DVB-80 [14,17,19,33] and N,N-methylenebisacrylamide [34][35][36][37]. EGDMA is a hydrophilic crosslinking agent with more polar characteristic compared to the DVB-80.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the utilization of EGDMA as a crosslinking agent in AN-VBC copolymer system has never been reported before. It was widely reported that the most common crosslinkers that have been used in the polymeric system are DVB-80 [14,17,19,33] and N,N-methylenebisacrylamide [34][35][36][37]. EGDMA is a hydrophilic crosslinking agent with more polar characteristic compared to the DVB-80.…”
Section: Introductionmentioning
confidence: 99%
“…[62][63][64] The polymerization of acrylic acid with a water-soluble crosslinker, e.g., 1% N,N 0 methylenebisacrylamide in an aqueous solution, is a straightforward process. 65 PAM hydrogels can also be crosslinked by gamma irradiation. 66 Toxic compounds as crosslinking agents have adverse effects on the environment as well as undesirable reactions with the bioactive substances in the hydrogel matrix.…”
Section: Cardiomyocytes and Matrix Elasticitymentioning
confidence: 99%
“…The particles are approximately spherical with a rough surface of diameter ~ 300 nm. The plausible reason is that during polymerization, the ability of the remaining C = C on the surface of P(MBAm-co-MAA) was not e cient enough from the solution to form bonds with newly formed oligomers, which results in the morphology of cauli ower-like particles with the rough surface(Liu et al 2007, Liu et al 2018b…”
mentioning
confidence: 99%